2015
DOI: 10.1016/j.febslet.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles inS‐adenosyl‐l‐methionine binding and catalysis for active site residues of the thiostrepton resistance methyltransferase

Abstract: Resistance to the antibiotic thiostrepton, in producing Streptomycetes, is conferred by the S-adenosyl-l-methionine (SAM)-dependent SPOUT methyltransferase Tsr. For this and related enzymes, the roles of active site amino acids have been inadequately described. Herein, we have probed SAM interactions in the Tsr active site by investigating the catalytic activity and the thermodynamics of SAM binding by site-directed Tsr mutants. Two arginine residues were demonstrated to be critical for binding, one of which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
(87 reference statements)
2
1
0
Order By: Relevance
“…This conformation resembles that in other ligand-bound structures of SPOUT family members 39, 46 . Because the two cofactors adopt similar conformations, we focus our discussion on the structure bound to SAM.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…This conformation resembles that in other ligand-bound structures of SPOUT family members 39, 46 . Because the two cofactors adopt similar conformations, we focus our discussion on the structure bound to SAM.…”
Section: Resultssupporting
confidence: 68%
“…Each of the two cofactors (SAM and sinefungin) binds to RlmH in a bent conformation in which the amino-acid moiety of the cofactor folds toward the adenine base (Figs 1 and S3 ). This conformation resembles that in other ligand-bound structures of SPOUT family members 39 , 46 . Because the two cofactors adopt similar conformations, we focus our discussion on the structure bound to SAM.…”
Section: Resultssupporting
confidence: 68%
“…In contrast, thiopeptides with 26-membered macrocycles (e.g., thiostrepton, siomycin, nosiheptide, berninamycin, and thiocillin/micrococcin) target the 50S subunit of by interacting with the 23S rRNA and ribosomal protein L11. ,, Binding is mediated primarily by interaction with 23S rRNA and is cooperative with L11. Resistance to thiopeptides of this variety occurs through mutation of either 23S rRNA or L11. , Alternatively, methylation of the 23S rRNA also confers resistance. Improving initial models, , more recent structural studies based on NMR, X-ray crystallography, and molecular modeling showed that these 26-membered thiopeptides bind to a cleft between the 23S rRNA and L11, , but covalent capture data suggest binding may be more on the surface of the rRNA and not between 23S/L11 . The interface of the 23S rRNA and L11 is called the “GTPase-associated center” and is crucial for ribosome function given its interaction with many translation factors. Consequently, the binding of thiopeptides with a 26-member macrocycle in this area can affect all phases of translation, but the most studied effects are on EF-Tu and EF-G during elongation. Inhibition of EF-Tu and tRNA delivery presumab...…”
Section: Thiopeptidesmentioning
confidence: 99%